2015
DOI: 10.3906/biy-1507-79
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin increased vitamin C and antioxidant enzyme values in the plasma,heart, liver, and kidney of Adriamycin-treated rats

Abstract: IntroductionAdriamycin is an important chemotherapeutic agent used for treatment of some cancer varieties, but it has seriously toxic effects in especially in the heart (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Vitamin C is a key modulator of platelet (PLT) function but its effect on platelet width is not known. The decrease in mean platelet values of vitamin C study group is in line with a study carried out by [29]. It was stated in the study that vitamin C may affect the values of PLT, MPV, PCT and RDW.…”
Section: Discussionsupporting
confidence: 88%
“…Vitamin C is a key modulator of platelet (PLT) function but its effect on platelet width is not known. The decrease in mean platelet values of vitamin C study group is in line with a study carried out by [29]. It was stated in the study that vitamin C may affect the values of PLT, MPV, PCT and RDW.…”
Section: Discussionsupporting
confidence: 88%
“…Lipid peroxidation was also observed in mice treated with ADR [ 55 ]. Moreover, ADR caused excessive production of ROS and decreased activities of CAT, SOD, GSH-Px, GR, and MPO [ 56 ]. Melatonin had protective effects on hepatotoxicity induced by ADR in rats.…”
Section: Protective Effects Of Melatonin On Liver Injuriesmentioning
confidence: 99%
“…Melatonin had protective effects on hepatotoxicity induced by ADR in rats. The decrease in GSH concentration was significantly prevented and the activities of the enzymes mentioned above were improved by melatonin treatment [ 55 , 56 ]. Additionally, histopathological alterations reflecting hepatic dysfunction were significantly improved by melatonin [ 57 ].…”
Section: Protective Effects Of Melatonin On Liver Injuriesmentioning
confidence: 99%
“…The results recorded in the present study are in agreement with the findings of Elbe et al (2015) who reported that melatonin significantly increased SOD activity, GSH concentration and decreased MDA concentration in liver of diabetic rats. Also Karakilik et al (2015) stated that melatonin significantly increased SOD activity, GSH concentration in liver and kidney of Adriamycin treated rats. This antioxidant effect of melatonin may be due to its ability to cross different physiological barriers easily as a result of its lipophilic and hydrophilic criteria (El-Sokkary et al 2006), its free radical scavenging power As well as Its ability to deactivate other oxidant compounds (Park et al 2013).…”
Section: Discussionmentioning
confidence: 95%